ANALISIS KEPUASAN PELANGGAN MENGGUNAKAN METODE SERVQUEL PADA PELAYANAN @ Dapoer _Nides - Wahyu, Wahyu; Junenah, Junenah (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2021)
The purpose of the study was to determine the gap between the perceptions and expectations of service users towards the @dapoer_nides service and to find out what efforts should be made by the @dapoer_nides service to improve service quality.This SERVQUAL method identifies service quality as how far the difference between reality and expectations for the service customers receive (Parasuraman & Berry, 1985). The service quality of dapoer_nides shows that the value of the dimension of Empathy (Empathy) (0.805), Tangibles (Evidence) Real) (0.778) Assurance (0.710) Realibility (Reliability) (-1.038) and the gap value Responsiveness (Responsiveness) (-0.155). Meanwhile, the average gap value of respondents for each dimension is (1,483). This shows that the average respondent feels the level of the gap in the Realibility dimension is higher than the other dimension . ( service quality at dapoer _nides is not good, namely the quality of dimensions, namely tangibles (real evidence) with a value of 0.954 1, Realibility (Reliability) with a value of 0.936 1, , Assurance (guarantee) 0.959 1, and Empathy (Empathy) a value 0.953 1, while the dimension of Responsiveness with a value of 1.010 1 means that the quality is good.